Ethylene and Phloem Signals Are Involved in the Regulation of Responses to Fe and P Deficiencies in Roots of Strategy I Plants - Lucena, Carlos; Porras, Rafael; García, María J.; Alcántara, Esteban; Pérez-Vicente, Rafael; Zamarreño, Ángel M.; Bacaicoa, Eva; García-Mina, José M.; Smith, Aaron P.; Romera, Francisco J. (Frontiers in Plant Science, 2019)
Iron (Fe) and phosphorus (P) are two essential mineral nutrients whose acquisition by plants presents important environmental and economic implications. Both elements are abundant in most soils but scarcely available to plants. To prevent Fe or P deficiency dicot plants initiate morphological and physiological responses in their roots aimed to specifically acquire these elements. The existence of common signals in Fe and P deficiency pathways suggests the signaling factors must act in conjunction with distinct nutrient-specific signals in order to confer tolerance to each deficiency. Previous works have shown the existence of crosstalk between responses to Fe and P deficiency, but details of the associated signaling pathways remain unclear. Herein, the impact of foliar application of either P or Fe on P and Fe responses was studied in P- or Fe-deficient plants of Arabidopsis thaliana, including mutants exhibiting altered Fe or P homeostasis. Ferric reductase and acid phosphatase activities in roots were determined as well as the expression of genes related to P and Fe acquisition. The results obtained showed that Fe deficiency induces the expression of P acquisition genes and phosphatase activity, whereas P deficiency induces the expression of Fe acquisition genes and ferric reductase activity, although only transitorily. Importantly, these responses were reversed upon foliar application of either Fe or P on nutrient-starved plants. Taken together, the results reveal interactions between P- and Fe-related phloem signals originating in the shoots that likely interact with hormones in the roots to initiate adaptive mechanisms to tolerate deficiency of each nutrient.